Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

The quadratic polynomial if the zeroes are α and β

x² - (α + β)x + αβ

here α = 2 and β = -3

⇒x² - (-1)x + (-6)

⇒x² + x - 6

∴ the quadratic polynomial is x² + x - 6.

x² - (α + β)x + αβ

here α = 2 and β = -3

⇒x² - (-1)x + (-6)

⇒x² + x - 6

∴ the quadratic polynomial is x² + x - 6.

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

If the zeroes are 2 and -3,

the polynomial is:

(x-2)(x-(-3))

= (x-2)(x+3)

= x² + x - 6

the polynomial is:

(x-2)(x-(-3))

= (x-2)(x+3)

= x² + x - 6